A new LQP alternating direction method for solving variational inequality problems with separable structure. (1st December 2016) - Bnouhachem, Abdellah; Hamdi, Abdelouahed; Xu, M. H.
Abstract: We presented a new logarithmic-quadratic proximal alternating direction scheme for the separable constrained convex programming problem. The predictor is obtained by solving series of related systems of non-linear equations in a parallel wise. The new iterate is obtained by searching the optimal step size along a new descent direction. The new direction is obtained by the linear combination of two descent directions. Global convergence of the proposed method is proved under certain assumptions. We show the O (1 /  t ) convergence rate for the parallel LQP alternating direction method.